Clozapine in the treatment of refractory schizophrenia: a practical guide for healthcare professionals. Issue 1 (4th September 2020) - Flanagan, R J; Lally, J; Gee, S; Lyon, R; Every-Palmer, S
Abstract: Background: Clozapine remains the only medication licensed for treating refractory schizophrenia. However, it remains underutilized in part due to concerns regarding adverse events. Sources of data: Published literature. Areas of agreement: Common adverse events during clozapine treatment include sedation, hypersalivation, postural hypotension, dysphagia, gastrointestinal hypomotility, weight gain, diabetes mellitus and dyslipidaemia. Rare but serious events include agranulocytosis, cardiomyopathy, myocarditis, pneumonia, paralytic ileus and seizure. Areas of controversy: It remains unclear how best to minimize clozapine-induced morbidity/mortality (i) during dose titration, (ii) from hypersalivation and (iii) from gastrointestinal hypomotility. It is also unclear how clozapine pharmacokinetics are affected by (i) gastrointestinal hypomotility, (ii) systemic infection and (iii) passive exposure to cigarette smoke. Whether monthly haematological monitoring needs to continue after 12 months of uninterrupted therapy is also a subject of debate. Growing points: There is a need for better management of serious clozapine-related adverse events in addition to agranulocytosis. There is also a need for better education of patients and carers, general practitioners, A&E and ITU staff and others of the problems posed in using clozapine safely. Areas timely for developing research: There is a need for more research on assessing clozapine dosage (i) as patients get older, (ii) with respect to exposure to cigarette smoke and (iii) optimizing response if adverse events or other factors limit dosage.